Recent advances in the role of CARM1 in skeletal muscle development, metabolism, and homeostasis maintenance - Xie, Xiaojing; Li, Menghuan; Zhang, Yue; Bao, Zhenwei; Yi, Xuejie (Frontiers in Cell and Developmental Biology, 2025)
The development, metabolism, and functional maintenance of skeletal muscle is a complex dynamic balance process. Its imbalance may lead to muscular dystrophy, muscle atrophy, and other diseases, which seriously affect human health. Therefore, in-depth exploration of the regulatory mechanisms governing skeletal muscle homeostasis and the identification of effective therapeutic targets have garnered significant attention. Recent studies reveal that the protein arginine methyltransferase CARM1 plays a central regulatory role in skeletal muscle biology. Substantial evidence indicates that abnormal CARM1 expression and activity disrupt muscle regeneration, metabolic balance, and stress responses, leading to muscle functional decline. This highlights its indispensable role in maintaining skeletal muscle homeostasis. Furthermore, exercise—an effective intervention for improving muscle quality and function—may exert its beneficial effects through mechanisms closely linked to CARM1 function. Therefore, this review systematically summarizes the roles of CARM1 in skeletal muscle development, regeneration, material metabolism, and homeostasis based on its molecular structure and fundamental functions. It further explores CARM1’s functional manifestations in muscle atrophy and exercise adaptation, providing a theoretical framework for comprehensively understanding its pivotal role in physiological adaptation and muscle diseases, while evaluating its potential value as a therapeutic target.